Dry matter intake and production efficiencies of dairy cows rotationally grazing a perennial ryegrass monoculture, a perennial ryegrass-white clover sward, or a multispecies sward - A. Jezequel; L. Delaby; Z.C. McKay; J.T. Tobin; B. Horan (Journal of Dairy Science)
ABSTRACT: The objective of this study was to evaluate the effect of sward diversity on individual cow DMI, milk production, and milk production efficiency. In this context, 3 swards were compared: a perennial ryegrass monoculture (Lolium perenne L.; PRG), a PRG with white clover (Trifolium repens L.; PRGWC), and a multispecies sward (MSS) composed of grasses, legumes, and herbs. The experiment followed a randomized block design, encompassing 56.1 ha divided into 20 blocks. Three herds of 49 dairy cows were created, 1 for each sward, and were composed of both pure Holstein-Friesian (HF) and HF crossbred with Jersey (JFX) dairy cows. All the cows were distributed among the 3 treatments according to parity, expected calving date, overall Economic Breeding Index, and milk subindex within each breed. The study monitored pasture production and quality, milk production, DMI, and feed conversion efficiency over a 2-yr period. Results indicated that pregrazing herbage yields and daily herbage allowance were similar across sward types. Daily milk yield (MY) was significantly influenced by sward type, with PRG yielding less than both PRGWC and MSS (13.9, 15.5, and 15.5 kg/cow, respectively). Sward type had a significant effect on DMI, with PRG having the lowest DMI (16.3 kg DM/cow), compared with MSS (18.7 kg DM/cow), which was the highest whereas PRGWC was intermediate (17.5 kg DM/cow). Consequently, feed efficiency was greatest for PRGWC [91 g/unité fourragère lait (UFL) intake], intermediate for the MSS (87 g/UFL), and lowest for the PRG (83 g/UFL). Breed also had a significant effect on MY and composition, with JFX having a lower MY than HF (14.6 and 15.3 kg/cow, respectively) but with increased milk fat (5.31% and 5.72%, respectively) and protein (4.08% and 4.24%, respectively) concentration. Consequently, milk solids (MlS) production was similar for the 2 breeds. The JFX animals were more feed efficient, producing 89 g MlS/UFL intake compared with 84 g for HF. The study highlighted the potential for more diverse swards to improve animal performances in grazing systems while reducing the use of chemical N fertilizer, therefore improving the sustainability of such systems.